(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The study of value of intellectual property rights in engineering sectors has its own value in recent scenario. The interconnection between intellectual property rights and engineering sector has been focused so as to give much importance to mush rooming of invention in various branches of engineering. The stringent policy of IPR regarding scrutinization of patent application in order to prevent the ever greening patents has attained special connotation for the purpose of having stronger protection of intellectual property rights.